2015
DOI: 10.1016/j.molcel.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Dicer-TRBP Complex Formation Ensures Accurate Mammalian MicroRNA Biogenesis

Abstract: Summary RNA-mediated gene silencing in human cells requires the accurate generation of ∼22-nucleotide microRNAs (miRNAs) from double-stranded RNA substrates by the endonuclease Dicer. Although the phylogenetically conserved RNA-binding proteins TRBP and PACT are known to contribute to this process, their mode of Dicer binding and their genome-wide effects on miRNA processing have not been determined. We solved the crystal structure of a human Dicer–TRBP interaction complex comprising two domains of previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
250
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(275 citation statements)
references
References 47 publications
20
250
0
5
Order By: Relevance
“…4D, lower panel) indicating that either dimer formation is required to generate the dmDcr1-binding site on Loqs or that dimerization and dmDcr1 binding are alternative processes requiring the same protein surface. In agreement with the latter model, it has been shown recently that TRBP-dsRBD3 forms a highly similar interaction surface, which is used for direct Dicer binding (Wilson et al 2015).…”
Section: Loqs Forms Homodimerssupporting
confidence: 63%
See 2 more Smart Citations
“…4D, lower panel) indicating that either dimer formation is required to generate the dmDcr1-binding site on Loqs or that dimerization and dmDcr1 binding are alternative processes requiring the same protein surface. In agreement with the latter model, it has been shown recently that TRBP-dsRBD3 forms a highly similar interaction surface, which is used for direct Dicer binding (Wilson et al 2015).…”
Section: Loqs Forms Homodimerssupporting
confidence: 63%
“…Both dsRBPs have been implicated in miRNA biogenesis and contain three dsRNA binding domains (dsRBDs). It has been demonstrated that TRBP uses its first and second dsRBD to interact with the Dicer-produced miRNA intermediate while the third dsRBD is a protein-protein interaction domain and utilized for the interaction with the helicase domain of Dicer (Daniels et al 2009;Wilson et al 2015). In Drosophila, miRNA and short interfering RNA (siRNA) pathways are separated and two specialized Dicers exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After their export into the cytoplasm, a further maturation step is executed by Dicer, assisted by TRBP, PACT, and Ago2 in a poised complex, by cleaving the precursor's loop and generating a short imperfect double-stranded RNA (dsRNA) stem (miRNA duplex) (Wilson et al 2015). Ago2 then orchestrates the last maturation step, preferentially incorporating one of the duplex RNA strands into the RISC, responsible for translational repression and RNA degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Human Dicer also associates with two different dsRNA-binding proteins, TRBP and PACT (17,18). These dsRNA-binding proteins are not required for dicing activity but function as key regulatory factors in defining the dicing site and facilitating RISC formation (19)(20)(21).…”
mentioning
confidence: 99%